2010
DOI: 10.1080/07325223.2010.517483
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Changes in Counselor Self-Efficacy: Further Validation and Implications for Training and Supervision

Abstract: This study examines the changes in counselor self-efficacy beliefs during training. For this purpose, the Counseling Self-Estimate Inventory (COSE), based on Bandura's self-efficacy theory (1986), was employed (Larson et al.,1992). Both global counselor self-efficacy measures as well as specific measures related to five areas of counseling (i.e., micro skills, process, handling difficult client behaviors, cultural competence, and awareness of values) were analyzed. A total of 20 first-year MA students in couns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 34 publications
1
54
1
7
Order By: Relevance
“…Additionally, Tang et al (2004) reported that more coursework and internship experience were significantly correlated with higher levels of CSE. Similarly, Kozina, Grabovari, De Stefano, and Drapeau (2010) reported an increase in master's-level counseling students' CSE during their initial clinical work with clients. Regarding the relationship between CSE and supervision, Cashwell and Dooley (2001) reported higher levels of CSE in counseling students who received supervision as compared with those who did not.…”
mentioning
confidence: 96%
“…Additionally, Tang et al (2004) reported that more coursework and internship experience were significantly correlated with higher levels of CSE. Similarly, Kozina, Grabovari, De Stefano, and Drapeau (2010) reported an increase in master's-level counseling students' CSE during their initial clinical work with clients. Regarding the relationship between CSE and supervision, Cashwell and Dooley (2001) reported higher levels of CSE in counseling students who received supervision as compared with those who did not.…”
mentioning
confidence: 96%
“…Counselor self-efficacy has been given a great deal of attention in the counseling training literature (e.g., Kozina, Grabovari, De Stefano, & Drapeau, 2010), with varied results relating counselor self-efficacy to counselor performance. Although Heppner, Multon, Gysbers, Ellis, and Zook (1998) noted that the relationship between counselor self-efficacy and counseling process and outcome appears to be more complex than a simple "more self-efficacy is better philosophy" (p. 393), a number of studies associated counselor self-efficacy with variables related to counseling success (e.g., Lent, Hoffman, Hill, Treistman, Mount, & Singley, 2006).…”
mentioning
confidence: 99%
“…Counselor self-efficacy generally tends to improve with repeated practice [28]. However, in this sample, number of patients treated with CBT did not predict self-efficacy.…”
Section: Discussionmentioning
confidence: 43%